Ancient Goat Genomics: Structure, Selection, and Admixture - DALY, KEVIN (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2019)
The wild bezoar Capra aegagrus was brought under human control c. 8,000 BC, leading to the domestic goat Capra hircus. This livestock species remains in use 10,000 years later, and is of particular importance to communities in marginal and developing regions. Despite this long and significant shared history, our knowledge of the process of goat domestication is poor and reliant on modern populations. Using genomic data derived from over 80 ancient Capra remains from southwest Asia and Europe, the patterns of genetic diversity which characterize domestic goat through time are described. Neolithic goat populations appear to share a common ancestor, supporting a single domestication process. However, strong regional differentiation and direct tests of admixture indicate localized gene flow from the wild, contributing to goat genetic diversity in both ancient and modern populations and suggesting a domestication process featuring substantial interaction with diverse wild groups. A significant genetic turnover following the Neolithic time period is observed, most strikingly in the mitochondrial gene pool but also with nuclear genome evidence, supporting a homogenization of southwest Asian goat populations. A FST outlier scan identified several regions strongly differentiated in Neolithic goat populations, including regions close or overlapping the pigmentation genes KIT and KITLG and providing evidence for the early selection by farmers for prefered phenotypes. Genomic data from 14 historic Capra samples provides context to the genus, and suggests gene flow between domestic goat other Capra species. In addition, an Epipaleolithic genome from Direkli Cave, southern Turkey, is shown to have high affinity with the Caucasian Tur, suggesting divergent populations of Capra exist in the wild that have yet to be described. Finally, genomic data from a further 26 samples are suggestive of additional complexity in early goat herding, but indicate the geographic regions which must be studied to address unresolved questions regarding the history of domestic goat.
APPROVED
Keywords: Genomics; Goat